Strategi Peningkatan Layanan Publik Guna Meningkatkan Tingkat Kepuasan Publik : Sukolilo, Kecamatan Wajak, Kabupaten Malang, Provinsi Jawa Timur - Chavid Moyo Jaladri; Agus Wiastono (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
The aim of this research is to determine the problems of public service quality and develop strategies to improve the quality of public services through the principles of good governance at the Sukolilo District Office, Wajak District, Malang Regency, especially the principles of accountability, effectiveness, and efficiency. The research method used in this research is descriptive research with a qualitative approach, according to Miles and Huberman (Sugiono, 2013), intended to provide a clear picture of strategies for improving the quality of public services through the principles of good governance at the Sukolilo District Office, Wajak District, Malang Regency. Data collection techniques used document review and interviews with five informants based on the field studied, namely Sukolilo District leaders, Head of Government Affairs, service officers, and PAMOR. The results of this research indicate that improving the quality of public services at the Sukolilo District Office, Wajak District, Malang Regency in the aspect of accountability is quite good. This is based on existing service programs and policies such as prioritizing community needs, constant supervision, and community empowerment through morning assembly. However, there is still a need to improve regulations for empowering and monitoring employee performance and improving the provision of service facilities and infrastructure. Meanwhile, public services at the Sukolilo District Office, Wajak District, Malang Regency, in terms of effectiveness and efficiency, are also quite good. However, there is still a need for improvement in supervision and assessment of employee performance, training as computer operators related to services, and improvement in coordination between units and agencies.